Genome-to-genome analysis reveals associations between human and mycobacterial genetic variation in tuberculosis patients from Tanzania - Zhi Ming Xu; Michaela Zwyer; Hellen Hiza; Sarah Schmidiger; Mohamed Sasamalo; Miriam Reinhard; Anna Doetsch; Sonia Borrell; Olivier Naret; Sina Rüeger; Dylan Lawless; Simon Tang; et al. (BMC Medical Genomics)
Abstract The risk and prognosis of tuberculosis (TB) are influenced by a complex interplay between human and bacterial genetic factors. While previous genomic studies have largely examined human and bacterial genomes separately, we adopted an integrated approach to uncover host–pathogen interactions. We leveraged paired human and Mycobacterium tuberculosis (M.tb) genomic data from 1000 adult TB patients from Tanzania and used a “genome-to-genome” approach to search for associations between human and M.tb genetic variants and to identify interacting genetic loci. Our analyses revealed two significant host–pathogen genetic associations. The first significant association (p = 4.7e-11) links a human intronic variant in PRDM15 (rs12151990), a gene involved in apoptosis regulation, with an M.tb variant in Rv2348c (I101M), which encodes a T cell-stimulating antigen. The second significant association (p = 6.3e-11) connects a human intergenic variant near TIMM21 and FBXO15 (rs75769176) – also associated with TB severity (p = 0.04) – with an M.tb variant in FixA (T67M). While FBXO15 is involved in the regulation of antigen processing and TIMM21 affects mitochondrial function, FixA's role remains undefined due to limited functional characterization. Additionally, we observed that a group of M.tb T cell epitope variants were significantly associated with HLA-DRB1 variation, suggesting that, despite their rarity, certain epitopes may still be subjected to immune selective pressure. Together, these findings identify previously unknown sites of genomic conflicts between humans and M.tb, advancing our understanding of how this pathogen evades selection pressure and persist in human populations.